The effect of adjuvant radiotherapy on oncological outcomes in patients with early-stage cervical carcinoma with only intermediate-risk factors: a propensity score matching analysis. (3rd October 2022) - Turkmen, Osman; Kilic, Fatih; Tokalioglu, Abdurrahman Alp; Cakir, Caner; Yuksel, Dilek; Kilic, Cigdem; Boran, Nurettin; Kimyon Comert, Gunsu; Turan, Taner
Abstract: We aimed to evaluate whether adjuvant radiotherapy had a survival benefit for patients with early-stage cervical carcinoma with intermediate-risk factors. This study included patients who underwent radical hysterectomy and lymphadenectomy according to Wertheim–Okabayashi for stage IB1-IIA2 cervical carcinoma. Each patient had at least one intermediate-risk factor including tumour diameter ≥4 cm, deep stromal invasion, and positive lymphovascular space invasion (LVSI). Patients with lymph node metastasis, parametrial invasion, and positive surgical margins according to the final paraffin section were excluded. In total, 183 patients were included. Seventy-three (39.9%) patients had one, 85 (46.4%) had two, and 25 (13.7%) had three intermediate risk factors. Sixty-seven (36.6%) patients received adjuvant radiotherapy. There was a statistically significant difference in terms of stage, LVSI, and endometrial/uterine invasion between the groups that did and did not receive adjuvant radiotherapy ( p  = .024, p  = .018, and p  = .001, respectively). These two groups were homogenised by performing propensity score matching (PSM) analysis. In the new matched cohort ( n  = 134), 5-year disease-free survival (DFS) was 89.5% in the group that received adjuvant radiotherapy and 82% in the group that did not (HR: 0.484, 95% CI: [0.171–1.369]; p  = .171). Also, receiving adjuvant radiotherapy was not associated with an improvement in oncologic outcomes in patients with one, two, or more intermediate risk factors. In univariate analysis, none of the risk factors was associated with DFS. In conclusion, adjuvant radiotherapy had no favourable effect on survival outcomes in patients with early-stage cervical carcinoma with only intermediate risk factors. IMPACT STATEMENT: What is already known on this subject? Radiotherapy after radical hysterectomy in cervical carcinoma is accepted as the standard of care when high-risk factors – positive surgical margins, lymph node metastasis, and parametrial involvement – are found in the surgical specimen. However, the necessity of adjuvant radiotherapy in patients with intermediate-risk factors – deep stromal invasion, positive LVSI, tumour diameter ≥4 cm – is controversial. What do the results of this study add? We compared patients who received adjuvant radiotherapy and those who did not. No significant difference was found between the two groups in terms of oncologic outcomes. There was no difference between the two groups in terms of pelvic and extrapelvic recurrence rates. The number of positive intermediate-risk factors did not affect survival. Moreover, age, tumour type, stage, number of removed lymph nodes, grade, bilateral salpingo-oophorectomy, and endometrial/uterine invasion were not associated with DFS among patients with stage IB–IIA cervical carcinoma with only intermediate-risk factors. What are the implications of these findings for clinical practice and/or further research? Debate remains over the prognostic factors and the adjuvant treatment options in patients with early-stage cervical carcinoma who possess intermediate-risk factors. Adjuvant radiotherapy can be ignored if initial adequate surgery has been performed in this patient group.